Determinação experimental da força de adesão entre partículas e meios filtrantes constituídos de celulose - Faustino, Patrícia Brígida (Universidade Federal de São Carlos, 2010)
The influence of particle size, compression velocity, and of the material constituting the substrate on adhesion force between particle and substrate was investigated in this study. The centrifuge technique was applied for compression velocities (press-on) of 500, 1000, and 1500 rpm and detachment velocity (spin-off) of 500 to 14000 rpm. A microcentrifuge (MA 860, Marconi Equipamentos) of maximum rotational velocity of 1400 rpm was used during trials. The velocity of the centrifuge promoted the compression (press-on) and the detachment (spin-off) of particles on the surface of the substrate. Two tubes made of aluminum were placed in the rotor of the microcentrifuge to hold the adapters also made of aluminum. The adapters worked as supports for the substrate containing the particles of the particulate matter. After compression and after each decompression, pictures of the surface of the substrate containing the particles were taken and each image was analyzed in an image analysis program (Image-Pro Plus 6.0) in order to count adhered and detached particles. When it comes to evaluating the influence of particle-substrate adhesion force by using the centrifuge technique, phosphate concentrate (ρp=3.18 g.cm-3) was used as particulate matter. The diameter ranges studied for the particulate matter were of 9 22; 22,1 40; 40,1 54 and 54,1 77 μm. A cellulose filter paper and a cellulose ester membrane were used as substrate. The phosphate concentrate particles were pressed against the surface of the paper filter and of the membrane individually with help of the centrifuge at specific compression centrifuge velocities and, afterwards, the adhesion profile was determined. It was observed that the adhesion force increased with an increase in rotational velocity of the centrifuge applied in the compression and with an increase in particle size of the particulate matter. It was also verified that the adhesion force between the phosphate concentrate particles and the paper filter was higher than that of the membrane, which led to the conclusion that the structural arrangement of filter media had an influence on the detachment process of particles, consequently influencing on adhesion force value.
Keywords: Ar - poluição; Força de adesão; Técnica centrífuga; ENGENHARIAS::ENGENHARIA QUIMICA